Міжнародно-правовий захист культурних цінностей у зв'язку зі збройним конфліктом - Коваль, Дмитро Олександрович; Коваль, Дмитрий Александрович; Koval, Dmitry O. (My University, 2014)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.01.11- міжнародне право. - Національний університет «Одеська юридична академія», Одеса, 2014. Комплексно досліджено міжнародно-правовий захист культурних цінностей у зв'язку зі збройним конфліктом та простежено розвиток даного інституту міжнародного публічного права. Виявлено публічний інтерес у захисті культурних цінностей, встановлено зв'язок між ним та потенціалом співпраці держав на міжнародно-правовому рівні. Показано теоретичні підходи та виміри культурних цінностей, що розкривають сутність їх міжнародно-правового захисту та формування національної і міжнародної політики захисту: культурний націоналізм та інтернаціоналізм, власнісний та культурний аспекти цінностей. Проаналізовано дефініцію «культурні цінності» у співставленні з близькими термінами. Розглянуто доктрину захисного втручання. Постатейно прокоментовано та піддано конструктивній критиці основні міжнародні договори у сфері захисту культурних цінностей, зокрема Гаазька конвенція 1954 року та два Протоколи до неї. Досліджено індивідуальну кримінальну відповідальність за злочини проти культурних цінностей та реституція (у тому числі компенсаторна реституція).

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.01.11 - международное право. - Национальный университет «Одесская юридическая академия», Одесса, 2014. Комплексно исследована международно-правовая защита культурных ценностей в связи с вооруженным конфликтом и развитие этого института международного публичного права. Выявлен публичный интерес в защите культурных ценностей, установлена связь между ним и потенциалом сотрудничества государств на международно-правовом уровне. Показано теоретические подходы и измерения культурных ценностей, раскрывающие сущность их международно-правового режима и формирование национальной и международной политики защиты: культурный национализм и интернационализм, собственнический и культурный аспекты ценностей. Проанализирована дефиниция «культурные ценности» в сопоставлении с близкими понятиями. Рассмотрена доктрина защитного вмешательства. Постатейно прокомментированы основные международные договоры в области защиты культурных ценностей, в частности Гаагская конвенция 1954 года и два Протокола к ней. Исследована индивидуальная уголовная ответственность за деликты против культурных ценностей и вопросы их реституции (в том числе компенсаторная реституция).

The thesis for the Candidate of Law Degree by specialty 12.00.01 - International Law. - National University "Odessa Academy of Law". - Odessa, 2014. The author comprehensively analyses the question of international law protection of cultural property in the event of armed conflict and evaluates the gradual development of the aforementioned. The reasons for existence of public interest in the protection of cultural property and its role in the potential cooperation of states are considered. The author assesses different theoretical approaches and perceptions, namely cultural nationalism and cultural internationalism, property and the cultural aspects of cultural property that altogether determines the status of cultural property in international law as well as national policy for their protection on the international law level. Protective intervention in relation to the said theoretical approaches and proposes to employ the doctrine of protective intervention in the modem peacekeeping missions and peace enforcement operations (the strategy of protection of cultural property have to be developed before the intervention; the obligation for the protection of cultural property cannot be transferred to the state of intervention - this is similar to the doctrine "responsibility while protecting") are reviewed. The definition of cultural property is compared with similar terms. The author examines the articles of the leading international instruments for die protection of cultural property, among them: The Hague Convention of 1954 and its two Protocols, the 1970 and 1972 UNESCO Conventions, Additional Protocols to the Geneva Conventions of 1977, the UNIDROIT Convention of 1995. The said instruments are discussed with regard to the positive and negative examples of fulfillment of their norms. Author evaluates the question of individual criminal responsibility for the acts against cultural property, considers three international crimes that can be qualified as the acts against cultural property: crimes against humanity, war crimes and genocide (the latter lacks uniformity of the views of scholars). The thesis examines restitution, including compensatory restitution which is qualified as an adequate measure of the responsibility of states under international law. The underdeveloped procedure of the compensatory restitution is named as the chief reason for criticism of its application.
Коваль Д. О. Міжнародно-правовий захист культурних цінностей у зв'язку зі збройним конфліктом : автореф. дис. ... канд. юрид. наук : 12.00.11 / Д. О. Коваль; кер. роботи Н. А. Зелінська; Нац. ун.-т "Одеська юридична академія". – Одеса, 2014. – 20 с.
Keywords: культурні цінності; культурна спадщина; інтернаціоналізм та націоналізм у захисті культурних цінностей; культурна власність; реституція; компенсаторна реституція; міжнародна кримінальна відповідальність; Гаазька конвенція 1954 року; Пакт Реріха; культурные ценности; культурное наследие; интернационализм и национализм в защите культурных ценностей; культурная собственность; реституция; компенсаторная реституция; международная уголовная ответственность; Гаагская конвенция 1954 года; Пакт Рериха; cultural property; cultural heritage; internationalism and nationalism in the protection of cultural property; restitution; compensatory restitution; the international criminal responsibility; the Hague Convention 1954; the Roerich Pact